2022
DOI: 10.3390/ijms23073421
|View full text |Cite
|
Sign up to set email alerts
|

EAPB0503, an Imidazoquinoxaline Derivative Modulates SENP3/ARF Mediated SUMOylation, and Induces NPM1c Degradation in NPM1 Mutant AML

Abstract: Nucleophosmin-1 (NPM1) is a pleiotropic protein involved in numerous cellular processes. NPM1 shuttles between the nucleus and the cytoplasm, but exhibits a predominant nucleolar localization, where its fate and functions are exquisitely controlled by dynamic post-translational modifications (PTM). Sentrin/SUMO Specific Peptidase 3 (SENP3) and ARF are two nucleolar proteins involved in NPM1 PTMs. SENP3 antagonizes ARF-mediated NPM1 SUMOylation, to promote ribosomal biogenesis. In Acute Myeloid Leukemia (AML), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Treatment of the NPM1-mutated AML cell lines OCI-AML3 with deguelin, a rotenoid isolated from several plant species [46,47], and IMS-M2 with (-)-epigallocatechin-3-gallate (ECGT) [48], a major catechin found in green tea, were effective in reducing the NPM1 mutant but not the wild-type protein and in inducing apoptosis. Moreover, the imidazoquinoxaline derivative EAPB0503 induced a selective proteasome-mediated degradation of NPM1 mutant protein through EAPB0503-mediated SUMOylation and ubiquitylation [49]. This event was followed by restoration of NPM1 wild-type protein in the nucleolus [50], apoptosis (through selective downregulation of HDM2 and activation of p53 [49]) and reduction of leukemia burden in NPM1-mutated AML xenografts [49,50].…”
Section: Targeting Npm1 Protein Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of the NPM1-mutated AML cell lines OCI-AML3 with deguelin, a rotenoid isolated from several plant species [46,47], and IMS-M2 with (-)-epigallocatechin-3-gallate (ECGT) [48], a major catechin found in green tea, were effective in reducing the NPM1 mutant but not the wild-type protein and in inducing apoptosis. Moreover, the imidazoquinoxaline derivative EAPB0503 induced a selective proteasome-mediated degradation of NPM1 mutant protein through EAPB0503-mediated SUMOylation and ubiquitylation [49]. This event was followed by restoration of NPM1 wild-type protein in the nucleolus [50], apoptosis (through selective downregulation of HDM2 and activation of p53 [49]) and reduction of leukemia burden in NPM1-mutated AML xenografts [49,50].…”
Section: Targeting Npm1 Protein Levelsmentioning
confidence: 99%
“…Moreover, the imidazoquinoxaline derivative EAPB0503 induced a selective proteasome-mediated degradation of NPM1 mutant protein through EAPB0503-mediated SUMOylation and ubiquitylation [49]. This event was followed by restoration of NPM1 wild-type protein in the nucleolus [50], apoptosis (through selective downregulation of HDM2 and activation of p53 [49]) and reduction of leukemia burden in NPM1-mutated AML xenografts [49,50]. Moreover, introducing NPM1-mutation into cells normally bearing wild-type NPM1 sensitized them to EAPB0503, leading to their growth arrest [50].…”
Section: Targeting Npm1 Protein Levelsmentioning
confidence: 99%
“…Most synthesized imidazoquinoxaline-based anticancer compounds have shown an anticancer activity towards diverse cancer cell lines. However, the in vitro activity of these compounds has been reported to be suboptimal [ 8 , 9 , 10 , 11 ]. Thus, despite the great anticancer potential, the clinical implementation of these compounds is still lacking due to safety concerns and expected outcomes in clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…[20] This further led to the development of EAPB203 and EAPB503 compounds, which are under clinical studies for further development. [21] Commercially, imidazoquinoxaline derivatives have profound applicability as dyes and luminescent materials. [22] In the last few years, several studies have been reported describing various synthetic strategies for the preparation of imidazoquinoxaline derivatives [23], such as π-conjugation of perylenes with external aromatic compounds, [24] solid phase and resin-based synthesis via a modified strategy for Pictet À Spengler reaction, [13,25] Van Leusen deprotectioncyclization, [26] using the microwave, [27] and cycloaddition of ethyl isocyanoacetate to 3-Chloro-2-(methylthio)/2-(methylsulfonyl) quinoxalines.…”
Section: Introductionmentioning
confidence: 99%
“…Imiquimod, marketed under the name Aldara®, is one of the first members of the imiqualines family that got approval for treatment of various types of cancer by the US FDA in 1997 [20] . This further led to the development of EAPB203 and EAPB503 compounds, which are under clinical studies for further development [21] . Commercially, imidazoquinoxaline derivatives have profound applicability as dyes and luminescent materials [22] .…”
Section: Introductionmentioning
confidence: 99%